2021
DOI: 10.34293/education.v9i2.3552
|View full text |Cite
|
Sign up to set email alerts
|

Practitioners’ Opinions on Student Assessment Process in Distance Education in the Context of Educational Technologies

Abstract: The aim of this study is to reveal the views of the practitioners regarding the measurement and evaluation sub-system of distance education applications in higher education. 11 faculty members working at Akdeniz University, determined with an easily accessible sampling of purposeful sampling methods, participated in this study in which qualitative research method was used. The research is in case study design, one of the qualitative research designs. Therefore, to collect data, a semi-structured interview form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The generation of the result of the conceptual definition of evaluation is exemplified through the bibliographic survey carried out. It was concluded that, among the most found evaluation equivalence terms, the term "process," mentioned by six authors (Ferreira Neto et al, 2021;Trindade, 2018;Damiola, 2020;Muthmainnah et al,2021;Yörük, 2021;Wildner, 2021), showing that evaluation is a systematic and complete process in itself.…”
Section: Results Generation Strategymentioning
confidence: 99%
See 4 more Smart Citations
“…The generation of the result of the conceptual definition of evaluation is exemplified through the bibliographic survey carried out. It was concluded that, among the most found evaluation equivalence terms, the term "process," mentioned by six authors (Ferreira Neto et al, 2021;Trindade, 2018;Damiola, 2020;Muthmainnah et al,2021;Yörük, 2021;Wildner, 2021), showing that evaluation is a systematic and complete process in itself.…”
Section: Results Generation Strategymentioning
confidence: 99%
“…The literature review showed that process is the most frequent evaluation equivalence term (Ferreira Neto, 2021;Trindade, 2018;Damiola, 2020;Muthmainnah et al, 2021;Yörük, 2021;Wildner, 2021). The process is a sequence of steps, each with its specific way of being executed.…”
Section: What Is Evaluationmentioning
confidence: 99%
See 3 more Smart Citations